Convention between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Republic of Cyprus for the Elimination of Double Taxation with respect to Taxes on Income and on Capital Gains and the Prevention of Tax Evasion and Avoidance, Nicosia, 22 March 2018. ([2018-08-06]) - Unknown
No abstract available